Application of paleoecological statistical methods based on benthic foraminifera for the determination of paleoenvironmental changes - Dimiza, M.; Drinia, H.; Antonarakou, A.; Tsaparas, N.; Dermitzakis, M.D. (6th Pan-Hellenic Geographical Conference of the Hellenic Geographical Society, 2002)
Benthic foraminifera widespread occurrence, numerical abundance and high fossilization potential rank them among the most powerful biological tools to reconstruct paleoenvironments. Their diversity and composition by suborder sometimes provide a general indication of the past environment, but the benthic taxonomic composition and recognition of faunal assemblages allow more detailed assessments of water depth, intertidal level, salinity, exposure to water turbulence, bottom oxygen concentrations, water temperature and carbon flux. The distribution of benthic foraminifera group is determined, and an analysis of the data is made in an effort to isolate and identify  important relationships between the distribution of organisms studied and the parameters of the physical environment. Benthic Foraminifera of the Upper Pliocene Tsoutsouras section (southern Crete) are analysed in order to investigate their relationship with paleodepth, sediment grain size and climatic changes. This paper encompasses the first detailed quantitative paleoenvironmental analysis based on benthic foraminifera from this area. Q-mode analysis revealed the existence of three associations. A. beccarii-Miliolids association corresponds to a rather shallow marine environment with vegetation in the neighbourhood. A. planorbis-Agglutinants is characterized by a decline in the salinity and the existence of moderate environmental stress which is associated by oxygen depletion and increase of primary productivity. In the upper part of the section V.bradyana – C. carinata association represents theestablishment of a restricted environment with abundant nutrient, where organic matter accumulates and infaunal opportunistic species capable of surviving in stressed conditions dominate.